Babesia microti: Pathogen Genomics, Genetic Variability, Immunodominant Antigens, and Pathogenesis - Puri, Ankit; Bajpai, Surabhi; Meredith, Scott; Aravind, L.; Krause, Peter J.; Kumar, Sanjai (Frontiers in Microbiology, 2021)
Babesia are tick-borne hematoprotozoa belonging to the phylum Apicomplexa. More than 100 Babesia parasite spp. are found throughout the world and infect a wide array of wild and domestic animals. Seven Babesia spp. have been found to cause human disease. Babesia microti, the most common pathogenic Babesia species, is endemic in the Northeastern and upper Midwestern United States and is sporadically reported in other parts of the world. Most infections are transmitted by Ixodid (hard-bodied) ticks, although they occasionally can be spread through blood transfusion and rarely via perinatal transmission and organ transplantation. Babesiosis most often presents as a mild to moderate disease, however infection severity ranges from asymptomatic to lethal. Diagnosis is usually confirmed by blood smear or polymerase chain reaction (PCR). Treatment consists of atovaquone and azithromycin or clindamycin and quine and usually is effective but may be problematic in immunocompromised hosts. There is no human Babesia vaccine. Babesia microti genomic studies have only recently been initiated, however they already have delivered important new insights regarding the pathogen, population structure, and pathogenesis of the disease. Continued genomic research holds great promise for improving the diagnosis, management, and prevention of human babesiosis.